1988
DOI: 10.1136/jnnp.51.4.582
|View full text |Cite
|
Sign up to set email alerts
|

Reye-like syndrome following treatment with the pantothenic acid antagonist, calcium hopantenate.

Abstract: The patient (case 1) was a 72 year old female with multiinfarct dementia. Four months before our examination she had been started on a regimen of calcium hopantenate therapy (37 mg/kg/&). One day before the examination, with no prodromal symptoms, she developed severe nausea and vomiting, and then became stuporous. On examination her vital signs were as follows: temperature 35 6°C; pulse, 96 beats/min, respiration, 36/min, and BP, 160/70mmHg. She was deeply comatose and unresponsive to noxious stimuli. Pupils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It has been reported that treatment with the pantothenic acid antagonist calcium hopantenate caused Reye‐like syndrome (Noda et al . ; Shimizu et al . ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported that treatment with the pantothenic acid antagonist calcium hopantenate caused Reye‐like syndrome (Noda et al . ; Shimizu et al . ).…”
Section: Discussionmentioning
confidence: 95%
“…It is important to clarify whether vitamin transport via SLC5A6 is likely to be inhibited in practice by drugs in the therapeutic range of plasma concentration (nM-lM) to better understand the potential adverse effects in pharmacotherapy. It has been reported that treatment with the pantothenic acid antagonist calcium hopantenate caused Reye-like syndrome (Noda et al 1988;Shimizu et al 1990). Neurometabolic abnormality owing to pantothenic acid deficiency has been considered as one of the causes of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its dependence on PanK for metabolic activation, and its competition with Pan for this transformation, HoPan’s effective potency is expected to be highly dependent on the amount of Pan present in the environment. Indeed, the conflicting reports on HoPan’s toxicity in various animals and humans can be reconciled with a knowledge of the circulating levels of Pan in each case, and/or whether Pan was withheld from or added to the diet. ,,, Consequently, contrary to the conclusion of some of these early studies that HoPan induces a Pan deficiency, it is more likely that an underlying Pan deficiency resulted in an apparent increase in HoPan’s potency. One could therefore reasonably conclude that HoPan may be a potent inhibitor under conditions where Pan availability is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The most dangerous reactions were recorded after treatment with calcium hopantenate, some even fatal [ 78 ]. These included semicoma, Reye-like syndrome, and encephalopathy [ 77 ]. Gastrointestinal disorders and liver dysfunctions have been reported in the elderly [ 78 , 79 ].…”
Section: Pantothenic Acid/vb5 Bioavailability Dose and Efficiencymentioning
confidence: 99%